Surveillance of insecticide resistance in head lice using biochemical and molecular methods. Issue 9 (14th June 2006) - Thomas, D Rh; McCarroll, L; Roberts, R; Karunaratne, P; Roberts, C; Casey, D; Morgan, S; Touhig, K; Morgan, J; Collins, F; Hemingway, J
Abstract : Treatment of head louse infection is primarily through topical insecticides. However, there is growing evidence of resistance. A representative population sample was tested using biochemical and molecular methods; it was shown that, in Wales, treatments containing pyrethroids are likely to be less effective in controlling head louse infection than those containing organophosphates.